2020
DOI: 10.3390/coatings10100967
|View full text |Cite
|
Sign up to set email alerts
|

Soft Ion Sputtering of PAni Studied by XPS, AFM, TOF-SIMS, and STS

Abstract: Herein is a study of the soft sputtering method, gas cluster ion sputtering (GCIS), and its effects on the atomic, morphologic, and band structure properties of polyaniline (PAni) as studied with X-ray photoelectron spectroscopy (XPS), time-of-flight secondary ion mass spectrometry, atomic force microscopy, and scanning tunneling spectroscopy (STS). The GCIS source used was a 1000 argon atom cluster with 4 keV energy, which resulted in a sputter yield of 3.4 ± 0.2 × 10−3 nm3 per argon atom. Soft ion sputtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The deconvoluted C 1s can be fitted with five distinct peaks. The peak positioned at 284.6 eV accounts for C–C bonding, the peak located at 285.6 eV indicates C–NH 2 bonding, the peak observed at 286.6 eV corresponds to CN bonding, the peak located at 288.5 eV corresponds to CO bonding, and a small broad peak positioned at 290.9 eV corresponds to the π–π interactions between the GO sheets and PANI. The deconvolution spectrum of N 1s can be fitted with four distinct peaks, as shown in Figure c. The peaks positioned at 399 eV correspond to the NN bond of an azo compound, 398.4 eV corresponds to benzenoid amine bonding, 402 eV corresponds to the cationic radical of nitrogen (N + ) bonding, and 401.9 eV corresponds to C–N bonding .…”
Section: Resultsmentioning
confidence: 98%
“…The deconvoluted C 1s can be fitted with five distinct peaks. The peak positioned at 284.6 eV accounts for C–C bonding, the peak located at 285.6 eV indicates C–NH 2 bonding, the peak observed at 286.6 eV corresponds to CN bonding, the peak located at 288.5 eV corresponds to CO bonding, and a small broad peak positioned at 290.9 eV corresponds to the π–π interactions between the GO sheets and PANI. The deconvolution spectrum of N 1s can be fitted with four distinct peaks, as shown in Figure c. The peaks positioned at 399 eV correspond to the NN bond of an azo compound, 398.4 eV corresponds to benzenoid amine bonding, 402 eV corresponds to the cationic radical of nitrogen (N + ) bonding, and 401.9 eV corresponds to C–N bonding .…”
Section: Resultsmentioning
confidence: 98%
“…43 The high-resolution N1s spectrum of PANI/NFGO is shown in Figure 3d, its peak intensity was much higher than the N1s peak of NFGO (Figure S6). Moreover, the peaks corresponding to −NH−, −N�, and N+ were located at 398.4, 399.6, and 400.8 eV, respectively, 44,45 which were different from the pyridine N, pyrrole N, and graphite N configurations in the N1s peak of NFGO, respectively. The presence of N doping in graphene, as well as semi-ionic C−F bonding, significantly increased the electrical conductivity of the sample (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…23 Figure 6c displays the O 1 s spectrum, that deconvoluted into three peaks at 400.12 eV, 401.33 eV and 398.98 eV are ascribed to C-N=C, oxidized nitrogen and C-NH=C bonds. 24 The deconvoluted nitrogen shows the two board peaks at 399.48 eV and 400.76 eV which is corresponding to N atoms hybridized with carbon in the forms of pyridinic (N1) and pyrrolic (N2). 25 From this, the N-doped graphene has been correlated with Raman spectra and revealed that the nitrogen doping on graphene nanostructure would have the ability to enhance the electrocatalytic activity towards interaction with guanine and adenine.…”
Section: Resultsmentioning
confidence: 99%